2009
DOI: 10.1097/rct.0b013e31816c82bc
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Tuberculosis

Abstract: Pancreatic tuberculosis can present with a variable spectrum of imaging findings. Tuberculosis of the pancreas should be considered as a diagnostic possibility in patients who present with a pancreatic space occupying lesion associated with peripancreatic lymphadenopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 11 publications
1
37
0
Order By: Relevance
“…Our patient presented with non-specific epigastric pain and constitutional features consistent with the published literature to date on pancreatic TB [4, 5, 7, 9]. He had non-specific markers of chronic inflammatory disease/TB in the form of anaemia, elevated ESR and a positive tuberculin skin test.…”
Section: Discussionsupporting
confidence: 76%
“…Our patient presented with non-specific epigastric pain and constitutional features consistent with the published literature to date on pancreatic TB [4, 5, 7, 9]. He had non-specific markers of chronic inflammatory disease/TB in the form of anaemia, elevated ESR and a positive tuberculin skin test.…”
Section: Discussionsupporting
confidence: 76%
“…In spite of the fact that pancreatic compromise by tuberculosis is rarely identified at imaging studies, at least one series has reported a prevalence of 8.3% of pancreatic involvement in 384 patients with diagnosis of abdominal tuberculosis. The described alterations include increased pancreas dimensions ( Figure 10 ), hypodense intrapancreatic collections or complex masses, besides peripancreatic lymphadenopathy ( 25 ) .…”
Section: Pancreasmentioning
confidence: 99%
“…[ 3 , 4 ] Although majority of cases occurred as a part of disseminated tuberculosis, about half of patients denied a previous history of tuberculosis infection and more than half showed normal findings on chest radiographs. [ 4 , 5 , 11 , 12 ]…”
Section: Discussionmentioning
confidence: 99%